Expert System Certainty Factor Method in Website-Based Pest Diagnosis of Eggplant Plants: Expert System Certainty Factor Method in Website-Based Pest Diagnosis of Eggplant Plants - Malik Abdul Aziz Sujudi; Fauziah Fauziah; Deny Hidayatullah (Institute of Computer Science (IOCS), 2020)
Eggplant crop cultivation is often influenced by various factors, factors that often occurs is pests and diseases. Lack of information and still rely on the experience of farmers to deal with pests and disease is a major cause. This problem is particularly serious because the can lead to crop failure. In this research, expert systems to diagnose pests and diseases eggplant created to help farmers cope with the problem - a problem that occurs in terngnya garden and provide solutions and suggestions prevention caused by pests and diseases. Certainty factor method is suitable for expert systems to diagnose disease eggplant crop is because these methods produce results of the highest percentage of belief an expert.